2015
DOI: 10.1080/15226514.2015.1131229
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation potential of some halophytic species for soil salinity

Abstract: Phytoremediation potential of six halophytic species i.e. Suaeda nudiflora, Suaeda fruticosa, Portulaca oleracea, Atriplex lentiformis, Parkinsonia aculeata and Xanthium strumarium was assessed under screen house conditions. Plants were raised at 8.0, 12.0, 16.0, and 20.0 dSm(-1) of chloride-dominated salinity. The control plants were irrigated with canal water. Sampling was done at vegetative stage (60-75 DAS). About 95 percent seed germination occurred up to 12 dSm(-1) and thereafter declined slightly. Mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…This species is commonly found in moist areas with high salinity, pH, Na and Cl (Chenchouni, 2017), while S. fruticosa plants can withstand salinity levels up to 300 mM NaCl through the increase of sugars, proline and proteins content (Hameed et al, 2012). According to Devi et al (2016) this species is a salt hyperaccumulator and can be used for phytoremediation of saline soils. Regarding the nutritional value of S. frtuticosa, its seeds contains about 25% oil that can be used for human consumption, while its leaves are edible and used for human consumption or as forage (Weber, Ansari, Gul, & Ajmal Khan, 2007).…”
Section: Suaeda Fruticosa Forsskmentioning
confidence: 99%
“…This species is commonly found in moist areas with high salinity, pH, Na and Cl (Chenchouni, 2017), while S. fruticosa plants can withstand salinity levels up to 300 mM NaCl through the increase of sugars, proline and proteins content (Hameed et al, 2012). According to Devi et al (2016) this species is a salt hyperaccumulator and can be used for phytoremediation of saline soils. Regarding the nutritional value of S. frtuticosa, its seeds contains about 25% oil that can be used for human consumption, while its leaves are edible and used for human consumption or as forage (Weber, Ansari, Gul, & Ajmal Khan, 2007).…”
Section: Suaeda Fruticosa Forsskmentioning
confidence: 99%
“…Phytoremediation potential of six halophytic species, viz., Atriplex lentiformis, Portulaca oleracea, Parkinsonia aculeata, Suaeda fruticosa, Suaeda nudiflora, and Xanthium strumarium, was evaluated under glass house conditions in Hisar, India ( Devil et al 2016). They found that all these plants are salt hyperaccumulators.…”
Section: Importance Of Halophytes In Phytoremediationmentioning
confidence: 99%
“…is a halophyte belonging to Amaranthaceae family, and it commonly occurs in areas with high salt concentration. Its seeds have significant quantity of oil used by humans for different purposes, while foliage is used as food or forage (Devi et al 2016).…”
Section: Suaeda Fruticosa Forssk (Shrubby Sea Blight)mentioning
confidence: 99%